Fine needle aspiration cytology - a powerful tool in the diagnosis of space occupying and mass lesions: a review - Chowdhury, Babul Osman; Ahamad, Md Shahab Uddin; Zobair, Mohammad (Journal of Chittagong Medical College Teachers' Association, 2009)
doi: 10.3329/jcmcta.v19i2.3873 Journal of Chittagong Medical College Teachers' Association 2008: 19(2):54-56